2017
DOI: 10.1002/jcb.26287
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 suppresses lipopolysaccharide‐induced inflammatory responses in rAW 264.7 macrophage cells through NF‐κB, AP‐1, and MAPKs signaling

Abstract: Gangliosides are known to specifically inhibit vascular leukocyte recruitment and consequent interaction with the injured endothelium, the basic inflammatory process. In this study, we have found that the production of nitric oxide (NO), a main regulator of inflammation, is suppressed by GM3 on murine macrophage RAW 264.7 cells, when induced by LPS. In addition, GM3 attenuated the increase in cyclooxyenase-2 (COX-2) protein and mRNA levels in lipopolysaccharide (LPS)-activated RAW 264.7 cells in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The NFκB is then phosphorylated and converted to its active form. In the NFκB signaling pathway, MAPK regulates the activation of NFκB; the phosphorylation of MAPK induces the activation of NFκB followed by subsequent expression of inflammatory mediators and pro-inflammatory cytokines [ 10 , 22 ]. To investigate the effect of atraric acid on the MAPK/NFκB signaling pathway, LPS-stimulated RAW264.7 cells were treated with atraric acid to analyze the expression of the inflammatory mediators by Western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NFκB is then phosphorylated and converted to its active form. In the NFκB signaling pathway, MAPK regulates the activation of NFκB; the phosphorylation of MAPK induces the activation of NFκB followed by subsequent expression of inflammatory mediators and pro-inflammatory cytokines [ 10 , 22 ]. To investigate the effect of atraric acid on the MAPK/NFκB signaling pathway, LPS-stimulated RAW264.7 cells were treated with atraric acid to analyze the expression of the inflammatory mediators by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…In the LPS stimulated inflammation, toll-like receptor-4 (TLR4) and MD-2 in macrophages form heterodimers that recognize common patterns of an LPS molecule [ 26 ]. Upstream signaling initiated from the interaction of LPS and TLR4 complex induced the activation of MAPKs/NFκB signaling pathway, which results in overexpression of inflammatory factors [ 22 ]. The overexpression of the inflammatory factors, such as enzymes iNOS and COX-2 and pro-inflammatory cytokines including TNF-α, IL-6, and IL-1β, induces cellular inflammatory responses and consequently leads to in vivo damage such as endotoxin shock ( Figure 8 ) [ 6 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that several gangliosides, such as GM3 and GD1a, trigger anti-inflammatory responses in LPS-stimulated RAW264.7 macrophages [ 43 , 44 ]. In the present study, we provided evidence that Hp-s1 had an anti-neuroinflammatory role in LPS-stimulated microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that tumor-shed ganglioside is a secretory factor regulating the phenotype of macrophages and consequently enhancing angiogenesis [12]. In addition, exogenous GM3 ganglioside can suppress the lipopolysaccharide (LPS)-induced inflammatory response in RAW264.7 cell line [13]. In macrophages and microglia, the ganglioside content available in the extracellular space modulates Toll-like receptor 4 (TLR4) mediated stimulation [14,15].…”
Section: Introductionmentioning
confidence: 99%